INTELLIGENT WEARABLE TECHNOLOGIES IN CLOTHING DESIGN: MODERN DIRECTION AND STRATEGIES OF DEVELOPMENT - Пашкевич, К. Л.; CHEN, Ying; Процик, Б. О. (Art and Design, 2023)
Purpose. This paper aims to explore the application of intelligent wearable technology in clothing. Methodology research is conditioned by a comprehensive study of the subject and includes: methods of analysis, synthesis, comparison, method of analyzing sources, comparative method. Results. This paper analyzes the application of intelligent wearable technology in clothing, and discusses the problems of electronic components and power supply, as well as the comfort and design of intelligent clothing. Intelligent wearable technology refers to electronic devices and computing systems integrated into clothing, providing users with enhanced functions and convenience. Intelligent wearable technology can be used to monitor human health, track sports activities, improve personal safety and enhance personal convenience. Research has found that intelligent wearable electronic components can help people track key health indicators and improve personal safety. In addition, intelligent wearable electronic components can also enhance personal convenience, such as controlling music, answering phone calls and monitoring information. From the perspective of fashion, intelligent wearable electronic components can be integrated into clothing design to create a unique and innovative fashion statement. However, electronic components and power supply are still the main difficulties of smart clothing. The scientific novelty. This paper proposes some solutions to minimize the shortcomings of current smart clothing, and provides new suggestions for the application of smart wearable technology in clothing in the future. Practical significance. The materials of the article can be used when studying the topic of clothing design using modern information technologies and innovations and when writing scientific papers.